Strategy and Policy on Dairy Cattle Development in Areas Outside Java Island in Supporting Domestic Fresh Milk Production - Dwi Priyanto; Dewi Rahmayuni (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
Production of domestic fresh milk has not yet meet the national milk demand, so high amount of milk is still imported (88.56%). The distribution of the dairy cattle population is still concentrated in Java Island (98.84%) which already has limited available land resources. The low productivity of dairy cow is due to the decline in the quality of breed, limited feed and capital. The business scale majority is still low, although its institutional aspect has been well established with the existence of cooperatives and the milk processing industry. This paper discusses the strategies and policies for developing dairy cows in areas outside Java which are appropriate from the upstream to the downstream aspects. The development of dairy cows in areas outside Java Island is still slow, even experiencing a population decline in the last 4 years by 66.21% compared to that in Java that has an increase of 22.09%. Barriers include weak human resource factors, lack of availability of feed (forages and concentrates), low milk productivity and quality, and the production market which is the main thing in dairy business has not been developed. There were many obstacles encountered when dairy cow development program in areas outside Java island was established. Therefore, it requires strategies and policies as well as steps that must be carried out on target. There are several things that need to be done, namely selecting the location, procuring the right breed, training the human resources (target breeders), planting forage and making concentrates, and the main thing is institutional development (upstream to downstream), especially institutions for milk production and marketing. Routine assistance by related agencies and other institutions is needed to ensure the sustainability of dairy farming outside Java.